The culture of enlightening: Abbé Claude Yvon and the entangled emergence of the Enlightenment - Burson, Jeffrey D. (University of Notre Dame Press, 2019)
The culture of enlightening en Sorbonne and the formation of Claude Yvon -- Into the midcentury maelstrom: Claude Yvon between Sorbonne and the encyclopédistes -- The Encyclopédie and the polarization of enlightening culture in France -- Yvon the encyclopédiste I: metaphysics, logic, and the history of philosophy -- Yvon the encyclopédiste II: immortality, immateriality, and an Abbé's dalliance with vitalistic materialism -- Yvon the encyclopédiste III: moral philosophy, practical theology, and the problem of evil -- Yvon in exile, 1752/1762 -- The return from exile, circa 1762/1768 -- The quest to harmonize philosophy and religion: the first attempt, 1762/1768 -- Out of the ashes? Yvon at Château d'Ormes, circa 1771/1774 -- From Yvon's last stand before the General Assembly of the Clergy to his last days, circa 1770/1789 -- Yvon postmortem: concluding reflections on the cultural and theological revolution of enlightening.